Dekolonialisasi Pendidikan Agama Kristen di Indonesia - Mariska Lauterboom (Asosiasi Teolog Indonesia, 2019)
This article explores the importance of decolonizing Christian religious education in Indonesia, especially in churches that were established during Dutch colonialism, by engaging in an expressly postcolonial and decolonial approach. After briefly tracing and criticizing the long history of Western colonialism concerning educational practice, this paper presents a variegated rationale connecting the content, relations, and methods within education in the present moment with those of the past—such that education today be seen as reflecting traces of the oppressive and colonizing education of yesteryear. The alternative to this is decolonization, by which a decolonial imagination attends that relational space of teaching-learning in order to transform and liberate Christian religious education in the postcolonial context of Indonesia. In this imagination, there is no body/mind dualism nor sacred/profane binary, and God is present to meet all as Liberator.